2018
DOI: 10.1111/1556-4029.13991
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Perceptions, and Preferences of Individuals from Temuco (Chile) About Denture Marking

Abstract: Denture marking (DM) helps identify edentulous people with different methods. Analyzing perceptions and attitudes of denture wearers would enable understanding of the practical aspects, an analysis still absent in South America. Fifty‐three individual candidates for removable dentures were instructed on disaster victim identification (DVI) and the usefulness of DM for this purpose. They were physically shown eight DM systems and a questionnaire to which they responded by highlighting preferences in those syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Chile is a country prone to natural disasters (Rojas-Torres et al, 2019); Moreno-Pascual (2010), regarding the earthquake and tsunami that devastated the Chilean coasts in February 2010, reported 5 cases in which individuals between 2 and 17 years old had to be identified through estimates of their ages and radiographic analysis. In two of those cases, the ranges of the estimates spanned more than 3 years (Moreno-Pascual, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chile is a country prone to natural disasters (Rojas-Torres et al, 2019); Moreno-Pascual (2010), regarding the earthquake and tsunami that devastated the Chilean coasts in February 2010, reported 5 cases in which individuals between 2 and 17 years old had to be identified through estimates of their ages and radiographic analysis. In two of those cases, the ranges of the estimates spanned more than 3 years (Moreno-Pascual, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been asserted that forensic dentists and oral health professionals can help prevent human rights violations through the application of best practice in human identification, and that human identification without complete post-mortem assessment can lead to delayed identifications thereby representing a violation of human rights and international humanitarian law (Smitha et al, 2019). Considering that Chile, a South American country with a long history of natural disasters (Rojas-Torres et al, 2019), has shown an unprecedented increase in the number of migrants in recent years with significant percentages of individuals under 18 years of age (Servicio Jesuita a Migrantes, 2019), the objective of this scoping review is to identify original studies describing radiographic methods for estimation dental age applied in Chilean children. The need to apply specific standards for this population as well as to update this information based on current populations to validate these methodologies are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of this job is denture marking, which has a significant potential for human identification after a catastrophe. 5,6 The denture's built-in marking could help with identification in a shorter amount of time. The dead are identified quickly, easing the emotional strain on mourning families and allowing them to complete their final goodbye rites as soon as possible.…”
Section: Denture Marking Systems Among Nepalese Dental Practitioners ...mentioning
confidence: 99%
“…2 Due to oral tissue preservation, the Removable partial dentures (RPDs) are a best choice as an alternate treatment option. 6,7 However, for most of the patients the fixed prosthesis is more desirable from a psychological point of view. 6,[8][9][10] Successful treatments by RPDs require thorough insight on the effect and interactions of the RPD with the oral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, for most of the patients the fixed prosthesis is more desirable from a psychological point of view. 6,[8][9][10] Successful treatments by RPDs require thorough insight on the effect and interactions of the RPD with the oral tissues. 4 The purpose of this article is to review the dental literature regarding Perio-prosthetic considerations in RPDs.…”
Section: Introductionmentioning
confidence: 99%